2009
DOI: 10.1111/j.1439-0531.2009.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofN-acetyl-cysteine andN-acetyl-cysteine-amide Supplementation onIn Vitro Matured Porcine Oocytes

Abstract: This study was conducted to evaluate the effects of different concentrations of the antioxidant N-acetyl-cysteine (NAC) supplemented to the maturation medium on porcine embryo development. Concentrations of NAC and its synthetic derivative, NAC-amide (NACA) were evaluated for effects on nuclear maturation, fertilization success and embryo development. Concentrations of NAC (0, 0.5, 1.0, 1.5, 2.0, 2.5 and 5.0 mm) were supplemented to maturing oocytes, and embryo development was analysed at 48 and 144 h post-fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
1
19
2
Order By: Relevance
“…Compared with previous studies conducted with other oxidants (Tatemoto et al. ; Whitaker and Knight ), the effects of sericin on the blastocyst formation rate was less potent. Although this discrepancy remains to be explained, this difference may reflect the difference in the culture system, such as the culture medium, culture conditions, and the presence of hormones and growth factors.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Compared with previous studies conducted with other oxidants (Tatemoto et al. ; Whitaker and Knight ), the effects of sericin on the blastocyst formation rate was less potent. Although this discrepancy remains to be explained, this difference may reflect the difference in the culture system, such as the culture medium, culture conditions, and the presence of hormones and growth factors.…”
Section: Discussioncontrasting
confidence: 82%
“…Earlier studies have demonstrated that the mediation of antioxidants to prevent damage to porcine oocytes caused by oxidative stress plays an important role in the acquisition of developmental competence after fertilization (Tatemoto et al. ; Whitaker and Knight ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic index and ROS genreation were also reversed by NAC in human ovarian cancer cells treated with WP 631, an anticancer anthracycline analog, and with doxorubicin, the best known first-generation anthracycline [50]. Another recent study [51] reported no differences in nuclear maturation, fertilization and cleavage rate, but higher blastocysts formation rate in presence of NAC compared with controls in porcine oocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Supplementing the oocyte maturation medium with 1.5 mM NAC or NACA N-acetyl-cysteine-amide has been shown to increase the percentage of development to the blastocyst stage [30]. However, the addition of NAC (0.6 mM) to the maturation medium did not improve the percentage of oocytes undergoing morula and blastocyst development.…”
Section: Effects Of Antioxidants On Mammalian Embryonic Developmentmentioning
confidence: 97%